Satzungsfiktion und Oktroi im neuen japanischen Gesellschaftsrecht - Westhoff, Jörn; Mayser, Andreas (Zeitschrift für Japanisches Recht, 2007)
On the basis of two examples, the article describes practical problems that occur with the newly revised corporate legislation. The objective of this revision was to adapt and simplify the legal situation, especially for small companies. However, in some special fields – the authors particularly examine the new rules about terms of office and the audit scope of auditors of small stock companies – the new corporation law provides some rather complicated stipulations. The legislators have chosen a very radical way of dealing with changes from the old to the new system of corporate legislation. Because the audit scope of auditors of small companies was widened by the Corporation Law, the legislators had to deal with the question of how the situation of the actual auditors should be ruled. For small closed companies, the law provides a legal fiction that automatically restricts the audit scope – which is, according to the Corporation Law, wider than before – in the articles of incorporation to the former size under the old provisions. However, this solution is not possible for small open companies because open companies in general are not allowed to restrict the audit scope in their articles of incorporation. Therefore, a statement of the Ministry of Justice provides that – by analogy – the term of office of all auditors of small open stock companies ended on the day of enforcement of the Corporation Law (i.e., May 1, 2006). The authors criticize this legislative path as an unnecessary and exceptionally severe interference in the corporate autonomy of small stock companies, and point out alternative ways of dealing with corporate legislation change in this context.